2009
DOI: 10.1007/s00018-009-0014-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional aspects of protein flexibility

Abstract: Proteins are dynamic entities, and they possess an inherent flexibility that allows them to function through molecular interactions within the cell, among cells and even between organisms. Appreciation of the non-static nature of proteins is emerging, but to describe and incorporate this into an intuitive perception of protein function is challenging. Flexibility is of overwhelming importance for protein function, and the changes in protein structure during interactions with binding partners can be dramatic. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
151
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(164 citation statements)
references
References 168 publications
6
151
0
Order By: Relevance
“…This increase in vibrational entropy might explain, at least in part, the increased entropy gain associated with adenophostin A binding. The larger T⌬S for adenophostin A relative to IP 3 binding would also be consistent with the larger apolar surface of adenophostin A, causing a greater entropy gain from ligand desolvation and hydrophobic interactions during binding (Teilum et al, 2009).…”
Section: Discussionmentioning
confidence: 68%
“…This increase in vibrational entropy might explain, at least in part, the increased entropy gain associated with adenophostin A binding. The larger T⌬S for adenophostin A relative to IP 3 binding would also be consistent with the larger apolar surface of adenophostin A, causing a greater entropy gain from ligand desolvation and hydrophobic interactions during binding (Teilum et al, 2009).…”
Section: Discussionmentioning
confidence: 68%
“…Nuclear magnetic resonance (NMR) spectroscopy is the key technique to study dynamics and conformational states of proteins in solution at atomic resolution 10,11 . NMR-based case studies [12][13][14] have indicated that the level of conformational exchange of amino-acid residues is directly related to their dynamics, with fast dynamics indicating fast interchange between many (different) conformations.…”
mentioning
confidence: 99%
“…Proteins possess many biological functions including binding, catalysis, operating as molecular switches, and serving as structural components of cells and organisms [1,2] and play an important role in the transportation and deposition of various endogenous and exogenous substances [3,4]. In recent years, the interaction of protein with small molecules has become a hot spot in the fields of chemistry, biology, and medicine [5][6][7].…”
Section: Introductionmentioning
confidence: 99%